2016
DOI: 10.1111/1744-9987.12447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intradialytic Resistance Exercise on Protein Energy Wasting, Physical Performance and Physical Activity in Ambulatory Patients on Dialysis: A Single‐Center Preliminary Study in a Japanese Dialysis Facility

Abstract: Patients under hemodialysis present protein-energy wasting (PEW), which is related with higher mortality rates. The study aimed to determine whether intradialytic resistance exercise training could improve physical performance, physical activity, and PEW in hemodialysis patients. In single center study, 75 hemodialysis patients were enrolled in an intradialytic resistance exercise training consisting of 20 min of adapted leg press, with a gymnastic ball, 3 days/week, during 9 months on the same day of hemodial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
2
20
0
3
Order By: Relevance
“…Some reports supposed that MAMC as a surrogate of LBM is a potential predictor of quality of life and survival of patients on maintenance HD and may be more important as a surrogate of body fat mass than TSF in predicting survival [ 10 , 27 ]. Based on this, studies on muscle-gaining interventions in patients on HD, such as intradialytic resistance exercise, were suggested for improving survival in the CKD population [ 1 , 17 , 28 ]. In addition, although some studies on the nutritional status of patients with ESRD have reported evaluation strategies and effective approaches for improving patient survival [ 25 , 29 33 ], clinical guidelines for improving muscle mass in patients on HD are warranted to promote better clinical outcomes in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports supposed that MAMC as a surrogate of LBM is a potential predictor of quality of life and survival of patients on maintenance HD and may be more important as a surrogate of body fat mass than TSF in predicting survival [ 10 , 27 ]. Based on this, studies on muscle-gaining interventions in patients on HD, such as intradialytic resistance exercise, were suggested for improving survival in the CKD population [ 1 , 17 , 28 ]. In addition, although some studies on the nutritional status of patients with ESRD have reported evaluation strategies and effective approaches for improving patient survival [ 25 , 29 33 ], clinical guidelines for improving muscle mass in patients on HD are warranted to promote better clinical outcomes in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lack of time, equipment, or place would be main a challenge of physical inactivity or exercise in dialysis patients; however, these may be overcame by exercise during dialysis sessions. Saitoh et al have recently investigated the effects of intradialytic exercise in dialysis [34]. Their preliminary results showed that intradialytic exercise was safe and improved physical activity and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria proposed by the International Society of Renal Nutrition and Metabolism (ISRNM) expert panel were used to classify PEW [11], which has been described elsewhere [22]. PEW was scored as the grading of 1 selected item in each of the four categories of wasting syndrome as follows: serum albumin, body mass index or unintentional weight loss, predialysis serum creatinine normalized by the body surface area (sCr/ BSA), and normalized protein nitrogen appearance (nPNA).…”
Section: Definition Of Pewmentioning
confidence: 99%